Quiet strength eaudiobook The principles, practices, and priorities of a winning life. - Dungy, Tony (Recorded Books Inc., 2008)
An NFL head coach and inspiration to millions, Tony Dungy scored a #1 New York Times best-seller with this remarkable memoir. When Dungy became the first African- American head coach to win the Super Bowl, he did it in the shadow of a great tragedy. But even through hardship, his fundamental decency and faith in God was readily apparent in everything he did.